The secret of the Christian way : a contemplative ascent through the writings of Jean Borella - Borella, Jean (SUNY series in Western esoteric traditions., 2001)
"Gathering key writings from the French religious philosopher Jean Borella's works, this book moves the reader from the immediacy of the physical world to a world deep within ourselves. Throughout Borella's writing, there is a "resurrectional" power to his words, a way of seeing things that "makes all things new," that endows us with an ability to look anew on Christ and his Body the Church. Translator and editor G. John Champoux has used a selection from Saint Bonaventure's The Soul's Journey into God to preface each of Borella's writings and to show how these insights can take us from our ordinary surroundings into our innermost world."--Jacket